Distribusi Spasial dan Determinan Kejadian HIV/AIDS di Propinsi Jawa Barat Tahun 2014 - Heriana, Cecep; Nurjannah, Siti Nunung; Suparman, Rossi (Sekolah Tinggi Ilmu Kesehatan Kuningan, 2015)
HIV/AIDS is a health problem in the West Java Province and unknown patterns of spatial detail until now. The objective of this study to determine the spatial Distribution and determinants of HIV/AIDS in West Java. Design cross-sectional study using secondary data from 2010 until 2013 with a sampleof 26 District/cities in West Java at January-Oktober 2015. Analysis used univariate and bivariate with the statistical test used was Chi-square and multivariate (regresi logistik). The result of this research shows the spatial distribution of HIV/AIDS prevalence, The highest prevalence of HIV and AIDS as 7 District/City in West Java and the lowest 19 District/cities in West Java . Statistical analysis showed that determinant of classification of the town ( p-value : 0.018 , 95 % CI : 0.001 to 0.089 ) , the type of highway ( P value : 1.000 , 95 % CI : 0.145 to 9047 ) , characteristics of the region ( p-value : 0.046 , 95 % CI : 0.001 to 1.027 ) and the use of condoms ( P value : 0.046 , 95 % CI : 0.826 to 56.504 ). The Conclusion is spatial distibusi highest HIV incidence in areas with tourist destinations and areas that have national lines ( north coast ) . There is a relationship between the classification of the town , characteristics of the region and the use of condoms with HIV/AIDS is dominant factor and there is no relationship between the type of highway with the HIV/AIDS in West Java.